The family context of assent: Comparison of child and parent perspectives on familial decision-making - Sibley, A; Fitzpatrick, R; Davis, E; Sheehan, M; Pollard, A (Wiley, 2017)
Assent guidelines currently fail to include an assessment of a child’s decision-making ability, experience and interest. This paper summarises a two-stage study, conducted in the United Kingdom, exploring perspectives on children’s decision-making power and ability within their family, as an indicator for overall decision-making readiness. Children desired to make some decisions but knew their parents held ultimate authority. Parents believed their children could make some decisions and actively trained them through involvement in daily decisions. Researchers should strive to include children in enrolment decisions to some degree, based on a consideration of their expectations for involvement informed by their daily family context.